Epidemiological features of nosocomial candidaemia in neonates, infants and children: A multicentre study in Iran. Issue 4 (20th March 2020) - Ahangarkani, Fatemeh; Shokohi, Tahereh; Rezai, Mohammad Sadegh; Ilkit, Macit; Mahmoodi Nesheli, Hassan; Karami, Hossein; Tamaddoni, Ahmad; Alizadeh‐Navaei, Reza; Khodavaisy, Sadegh; Meis, Jacques F.; Badali, Hamid
Summary: Nosocomial bloodstream candidaemia is a life‐threatening fungal infection with high morbidity and mortality, especially among paediatric patients undergoing intensive immunosuppressive therapy. Limited data on the epidemiology of candidaemia and susceptibility profiles are available for Iran. To characterise candidaemia epidemiology, comorbidity risk factors, species distribution, and antifungal susceptibility profiles among paediatric patients in Iran. This observational cross‐sectional study enrolled 26 189 patients <18 years old at three reference paediatric hospitals in Mazandaran and Tehran over 2 years. Blood samples from patients with suspected fungal bloodstream infection were analysed using the BACTEC culture system. Fungal isolates were identified using matrix‐assisted laser desorption ionisation time‐of‐flight mass spectrometry (MALDI‐TOF) and DNA sequencing. Antifungal susceptibility testing was performed using the Clinical and Laboratory Standards Institute broth microdilution guideline. We observed 109 episodes of nosocomial candidaemia in paediatric patients with or without immunosuppressive therapy. The most common healthcare‐associated factor was central vascular catheter use (97%). The all‐cause mortality rate was 40%, of which 48% was attributable to candidaemia. While Candida albicans was the most frequent causative agent (49%), emerging and uncommon Candida species were also isolated. Candidaemia mortality by non‐ albicans Candida species was significantly higher than that by C. albicans ( P  < .05). All fluconazole‐resistant species were non‐ albicans Candida species. Uncommon Candida species with reduced susceptibility to antifungals are emerging as major agents of nosocomial candidaemia in high‐risk paediatric patients in Iran. Appropriate source control, antifungal regimens and improved antifungal stewardship are warranted for managing and decreasing the burden of nosocomial candidaemia.